(untitled) (International Journal of Engineering and Computer Science, 2014)
Histogram Equalization is a technique that is basically used for Image Enhancement. It is a simple and effective technique that applied to the images captured in bright or dark environment thus becomes the low contrast images. The basic purpose of histogram is to produce the output image, which is much better in the form of appearance than the input image. This paper presents what is histogram and how it is being applied to the image for its enhancement and techniques used to perform Histogram Equalization (HE).